FACTORS RELATED TO QUALITY OF LIFE AFTER PERCUTANEOUS CORONARY INTERVENTION (PCI) IN PATIENTS WITH ATHEROSCLEROSIS HEART DISEASE - Jati, Ilham Pangestu; Sunaryo, Tri; Wulandari, Novita Kurnia (Journal of Vocational Nursing, 2025)
Introduction: Atherosclerotic heart disease is one of the leading cardiovascular diseases with a high mortality rate globally. Atherosclerosis occurs due to the accumulation of cholesterol and low-density lipoproteins (LDL) on the inner walls of blood vessels, forming plaques that can completely block arteries, potentially leading to death. One of the interventions used to relieve such blockages is percutaneous coronary intervention (PCI). PCI can have an impact on patients' physical activity and quality of life. The aim of this study is to determine the factors associated with quality of life after PCI in patients with atherosclerotic heart disease. Methods: This study employed a descriptive correlational research design with a cross-sectional approach. The sampling technique used was accidental sampling, resulting in a total of 60 respondents. Data were analyzed using the Spearman rank test and logistic regression. Results: The findings indicated that most respondents (81.7%) reported a moderate quality of life. Factors associated with quality of life after PCI included age, gender, education, anxiety, and illness perception. The results of the multivariate analysis revealed that the most significant factor associated with quality of life post-PCI was education, with an odds ratio (OR) of 9.392. Conclusions: Among all the factors, education emerged as the most dominant determinant of quality of life after PCI, with an odds ratio (OR) of 9.392 and a 95% confidence interval (CI) of 1.252–70.434.